2019
DOI: 10.1016/j.jcte.2019.100204
|View full text |Cite
|
Sign up to set email alerts
|

Liquid and softgel capsules of l-thyroxine results lower serum thyrotropin levels more than tablet formulations in hypothyroid patients

Abstract: ObjectiveEvidence indicates that L-T4 in liquid and softgel capsule are absorbed better than tablets in hypothyroid patients, even when patients are under medications that impair the intestinal absorption of L-T4. However, no study has evaluated all three L-T4 formulations in the same hypothyroid patients. This study aims to fill this gap. The outcome was the degree of TSH change in the liquid and softgel formulations, using tablet L-T4 as the reference, regardless of sequence of formulation and regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
1
15
0
3
Order By: Relevance
“…Four prospective studies with 200 participants evaluating replacement liquid LT4 therapy in hypothyroid patients and one population-based study with 56,354 patients treated with L-T4 mostly for hypothyroidism and non-toxic goitre were found [25][26][27][28][29]. In three out of four prospective studies including 185 subjects, switching from tablet LT4 to liquid LT4 appeared more effective; only in a single paper including 15 participants no difference in TSH between tablet and liquid LT4 formulations was noted [26].…”
Section: Comparison Of the Effectiveness Of Liquid And Tablet Levothymentioning
confidence: 99%
See 4 more Smart Citations
“…Four prospective studies with 200 participants evaluating replacement liquid LT4 therapy in hypothyroid patients and one population-based study with 56,354 patients treated with L-T4 mostly for hypothyroidism and non-toxic goitre were found [25][26][27][28][29]. In three out of four prospective studies including 185 subjects, switching from tablet LT4 to liquid LT4 appeared more effective; only in a single paper including 15 participants no difference in TSH between tablet and liquid LT4 formulations was noted [26].…”
Section: Comparison Of the Effectiveness Of Liquid And Tablet Levothymentioning
confidence: 99%
“…Five prospective observational studies were found evaluating liquid LT4 efficacy in 117 patients with malabsorption due to interfering drugs (proton pump inhibitors [PPIs], calcium, ferrous sulphate, polypharmacy) and a single prospective observational study assessing liquid LT4 results in 13 patients with malabsorption caused by bariatric surgery [38][39][40][41][42][43]. In five out of six studies patients were switched from tablet levothyroxine to the equivalent dose of liquid formulation.…”
Section: Efficiency Of Liquid Levothyroxine In Patients With Malabsormentioning
confidence: 99%
See 3 more Smart Citations